Effects of combined ketamine/xylazine anesthesia on light induced retinal degeneration in rats - Arango-Gonzalez, B; Schatz, A; Bolz, S; Eslava-Schmalbach, J; Willmann, G; Zhour, A; Zrenner, E; Fischer, M; Gekeler, F (Public Library of Science, 2012)
Objectives To explore the effect of ketamine-xylazine anesthesia on light-induced retinal degeneration in rats. Methods Rats were anesthetized with ketamine and xylazine (100 and 5 mg, respectively) for 1 h, followed by a recovery phase of 2 h before exposure to 16,000 lux of environmental illumination for 2 h. Functional assessment by electroretinography (ERG) and morphological assessment by in vivo imaging (optical coherence tomography), histology (hematoxylin/eosin staining, TUNEL assay) and immunohistochemistry (GFAP and rhodopsin staining) were performed at baseline (ERG), 36 h, 7 d and 14 d post-treatment. Non-anesthetized animals treated with light damage served as controls. Results Ketamine-xylazine pre-treatment preserved retinal function and protected against light-induced retinal degeneration. In vivo retinal imaging demonstrated a significant increase of outer nuclear layer (ONL) thickness in the non-anesthetized group at 36 h (p<0.01) and significant reduction one week (p<0.01) after light damage. In contrast, ketamine-xylazine pre-treated animals showed no significant alteration of total retinal or ONL thickness at either time point (p>0.05), indicating a stabilizing and/or protective effect with regard to phototoxicity. Histology confirmed light-induced photoreceptor cell death and Müller cells gliosis in non-anesthetized rats, especially in the superior hemiretina, while ketamine-xylazine treated rats showed reduced photoreceptor cell death (TUNEL staining: p<0.001 after 7 d), thicker ONL and longer IS/OS. Fourteen days after light damage, a reduction of standard flash induced a-wave amplitudes and a-wave slopes (p = 0.01) and significant alterations in parameters of the scotopic sensitivity function (e.g. Vmax of the Naka Rushton fit p = 0.03) were observed in non-treated vs. ketamine-xylazine treated animals. Conclusions Our results suggest that pre-treatment with ketamine-xylazine anesthesia protects retinas against light damage, reducing photoreceptor cell death. These data support the notion that anesthesia with ketamine-xylazine provides neuroprotective effects in light-induced cell damage.